2019 John Insall Award: Fructosamine is a better glycaemic marker compared with glycated haemoglobin (HbA1C) in predicting adverse outcomes following total knee arthroplasty: a prospective multicentre study. (July 2019) - Shohat, N.; Tarabichi, M.; Tan, T. L.; Goswami, K.; Kheir, M.; Malkani, A. L.; Shah, R. P.; Schwarzkopf, R.; Parvizi, J.
Abstract : Aims: The best marker for assessing glycaemic control prior to total knee arthroplasty (TKA) remains unknown. The purpose of this study was to assess the utility of fructosamine compared with glycated haemoglobin (HbA1c) in predicting early complications following TKA, and to determine the threshold above which the risk of complications increased markedly. Patients and Methods: This prospective multi-institutional study evaluated primary TKA patients from four academic institutions. Patients (both diabetics and non-diabetics) were assessed using fructosamine and HbA1c levels within 30 days of surgery. Complications were assessed for 12 weeks from surgery and included prosthetic joint infection (PJI), wound complication, re-admission, re-operation, and death. The Youden's index was used to determine the cut-off for fructosamine and HbA1c associated with complications. Two additional cut-offs for HbA1c were examined: 7% and 7.5% and compared with fructosamine as a predictor for complications. Results: Overall, 1119 patients (441 men, 678 women) were included in the study. Fructosamine level of 293 µmol/l was identified as the optimal cut-off associated with complications. Patients with high fructosamine (> 293 µmol/l) were 11.2 times more likely to develop PJI compared with patients with low fructosamine (p = 0.001). Re-admission and re-operation rates were 4.2 and 4.5 times higher in patients with fructosamine above the threshold (p = 0.005 and p = 0.019, respectively). One patient (1.7%) from the elevated fructosamine group died compared with one patient (0.1%) in the normal fructosamine group (p = 0.10). These complications remained statistically significant in multiple regression analysis. Unlike fructosamine, all three cut-offs for HbA1c failed to show a significant association with complications. Conclusion: Fructosamine is a valid and an excellent predictor of complications following TKA. It better reflects the glycaemic control, has greater predictive power for adverse events, and responds quicker to treatment compared with HbA1c. These findings support the screening of all patients undergoing TKA using fructosamine and in those with a level above 293 µmol/l, the risk of surgery should be carefully weighed against its benefit. Cite this article: Bone Joint J 2019;101-B(7 Supple C):3–9.